2014
DOI: 10.1063/1.4892578
|View full text |Cite
|
Sign up to set email alerts
|

High-performance chemical-bath deposited CdS thin-film transistors with ZrO2 gate dielectric

Abstract: We demonstrate high performance chemical bath deposited CdS thin-film transistors (TFTs) using atomic layer deposited ZrO 2 based high-k gate dielectric material. Our unique way of isolation of the CdS-based TFTs devices yielded significantly low leakage current as well as remarkable lower operating voltages (<5V) which is four times smaller than the devices reported on CdS-based TFTs using SiO 2 gate dielectric. Upon thermal annealing the devices demonstrate even higher performance, including  FE exceeding 4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Shan and co‐workers demonstrated that In 2 O 3 /ZrO x TFTs exhibit a saturation mobility of 3.08 cm 2 V −1 s −1 and an on/off current ratio of 10 8 . [12c] Pradhan and co‐workers fabricated CdS/ZrO x TFTs, which display a low operation voltage of 3.8 V and a field effect mobility of 4 cm 2 V −1 S −1 . Despite their attractive properties, the lower channel mobility still inhibits the realization of high‐performance ZrO x ‐based TFTs.…”
Section: Introductionmentioning
confidence: 99%
“…Shan and co‐workers demonstrated that In 2 O 3 /ZrO x TFTs exhibit a saturation mobility of 3.08 cm 2 V −1 s −1 and an on/off current ratio of 10 8 . [12c] Pradhan and co‐workers fabricated CdS/ZrO x TFTs, which display a low operation voltage of 3.8 V and a field effect mobility of 4 cm 2 V −1 S −1 . Despite their attractive properties, the lower channel mobility still inhibits the realization of high‐performance ZrO x ‐based TFTs.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Pradhan et al fabricated CdS TFTs with ZrO 2 as the gate dielectric grown by chemical bath, which exhibits a low operation voltage of 3.8 V and a field effect mobility of 4 cm 2 V −1 s −1 . 30 Despite their attractive properties, however, TFTs based on high-k gate dielectric are usually realized using stringent and potentially costly manufacturing techniques. 7 The development of solution-derived dielectrics is still a step behind, inhibiting the realization of fully solution-processed TFTs with high performance.…”
Section: Introductionmentioning
confidence: 99%
“…The TEC15 glass was cleaned by micro-90, deionized water, and dried by high purity N2 (99.999%, 5N). For CdS deposition, the sputter chamber was pumped to a base pressure of~10 -4 Pa. After that, the CdS was deposited at room temperature, 3 Pa, 0.88 W•cm -2 rf power, 28.3 cm 3 •min -1 Ar gas (high purity: 5N) together with 0 (0% (volume fraction, φ)), 0.25 (0.88% (φ) ), 0.5 (1.78% (φ)), 0.75 (2.58% (φ)), and 1 (3.40% (φ)) cm 3 •min -1 O2 gas (high purity: 5N). The thickness of the CdS was 100 nm measured by an in situ optical transmission thickness apparatus.…”
Section: Fabrication Of Cds and Absorb Layer Materialsmentioning
confidence: 99%
“…Cadmium sulfide (CdS) is an II-VI group semiconductor with a direct band gap of 2.4 eV (bulk CdS) at room temperature. 1 It has potential use in a wide range including photovoltaic cells, 2 thin-film transistors, 3 light-emitting diodes, 4 phosphors, 5 biological labeling, 6 etc. Due to its low electrical resistivity and high optical transmittance, CdS films are commonly used as a buffer layer material in thin film solar cells such as CdTe, CuInGaSe and so on.…”
Section: Introductionmentioning
confidence: 99%